ANALISIS PENGARUH BRAND KNOWLEDGE DAN CUSTOMER PREFERENCE TERHADAP BEHAVIOR INTENTION PADA FAST FASHION DI SURABAYA DENGAN BRAND CAUSE FIT SEBAGAI VARIABEL MEDIASI - Ruth Kristina (Jurnal Strategi Pemasaran, 2017)
This study examined whether brand knowledge and customer preference influence behavior intentiom through brandcause fit.This study uses quantitative causal research methods. The number of respondents were 190 consumer of the fastfashion with purposive sampling techique. Testing techniques of data used Partial Least Square (PLS). The technique of dataanalysis consisted of multivariate statististics techniques.For the next step, this research will explain the relation between brand knowledge and customer preference tobehavior intention of fast fashion.